Gambaran Pengetahuan Pasien Hipertensi Terhadap Penyakit Hipertensi Dan Obat Antihipertensi Golongan Ace-Inhibitor Dan Diuretik - Denia Pratiwi (LPPM Universitas Abdurrab, 2017)
Hypertension is a circumstances where patient having enhancement blood pressure above the normal rate was 120/80 mm/Hg. Hypertension is a disease can’t cured and can make many complication. One of pharmacology treatment can do for decrease blood pressure and prevent complication is using drug ACE-Inhibitor and diuretic group. The purpose of this research to know an overview of knowledge hypertension patient about the disease and drug ACE-Inhibitor and diuretic group.This is descriptif research using survey method, was done in Februari 2015 at UPTD Puskesmas Melur Pekanbaru with the number of respondent as much 81 patient consist of 50 respondent for ACE-Inhibitor group drug and 31 respondent for diuretic drug. Generally an overview of knowledge hypertension patient toward to hypertension disease was enough as much 38 patient (47%) and toward to ACE-Inhibitor group was less as much 30 respondent (60%) and to diuretic drug was enough as much 16 patient (52%). Keyword : Knowledge, Hypertension, ACE-Inhibitor drug an diuretic drug